Perceptions Of Clinical Placement Experience Among Diploma Nursing Students - Leong , Sui Wan; Chan , Siok Gim (Lincoln University College, Asia Pacific Higher Learning Sdn Bhd, 2014)
Clinical practice is an essential component of the nursing student's training. The practice allows nursing students the opportunity to relate theory into practice during nursing care to the patients. The aim of this project was to determine perceptions of clinical placement experience with respect to clinical practice, enhancement of learning and hindrance among nursing students. A total 254 participants undergoing training at Nursing College Kubang Kerian participated in this project. They were selected using the Raosoft sample size calculator. Survey questionnaires were distributed to 80 participants from ﬁrst year, 88 from second year and 86 participants from third year. The questionnaire consisting of 25 items with 5-point Likert Scale responses was used to measure nursing students' perceptions towards nurses during their clinical placement experience. In addition, demographic factors such as age groups, ethnicity, educational levels and years of training were examined. The items were pilot-tested and the Cronbach Alpha values obtained for clinical practice, enhancement of learning and hindrance consisting of 0.80, 0.80 and 0.83 respectively. The ﬁnal data was analysed using both descriptive and inferential statistics. Non-parametric Kruskal Wallis was used to make comparisons where sub samples were imbalanced. The level of signiﬁcance was set at 0.05. The results indicate that nursing students perceived their clinical placement positively. Perceptions towards clinical practice were signiﬁcantly different between nurses based on their residential areas and years of training. The results of this study revealed that there were challenges for the nursing educators, clinical instructors and other health providers in achieving a supportive clinical environment for the nursing students. (Abstract by authors)